Recognition of Customary Court: Perspective of Judicial Power and Special Autonomy of Papua - Reumi, Frans (Papua Law Journal, 2017)
The excellence of customary court for indigenous peoples of Papua as a peace justice institution which is one of the specific rights of Special Autonomy of Papua and it regulated in Article 50 paragraph (2) juncto Article 51 paragraph (1), and Article 43 paragraph (1) of Act No. 21 of 2001 in the field of executive. The recognition of customary court of Papua referred to as âtraditional rightsâ in accordance with Article 18B paragraph (2) juncto Article 24 paragraph (3) and Article 28I paragraph (3) of the 1945 Constitution, its relevance to Article 35 paragraph (3) letter d and Article 58 No. 48 of 2009 and in Article 1 No. (5) of Act No. 49 of 2009 is not synchronized for indigenous peoples of Papuan that perform the function of customary court in the Judicial Power system in the field of judicative informally. The object of this study is related to the primacy of the recognition of customary justice: perspective of judicial power and special autonomy of Papua by using normative juridical method. The results indicate the weakness of the recognition of customary court of Papua against: 1) the institutional of customary court, 2) authority and 3) the decision of customary court over the case or the customary dispute and the principle of ne bis in idem in the function of Judicial Power. Its implementation raises the conflict of norms on the Acts of Judicial Power and the Special Autonomy of Papua. For future, the customary court of Papua needs to be a synchronization of the legal basis of the relationship of authority recognition in the Act of Judicial Power and the Special Autonomy of Papua, in order to fulfill a sense of legal certainty and justice for indigenous people of Papua as multicultural and customary law as the living law.